2004
DOI: 10.1177/021849230401200206
|View full text |Cite
|
Sign up to set email alerts
|

Partial Cardiac Autotransplantation for Reduction of the Left Atrium

Abstract: Various surgical procedures have been employed to treat a greatly enlarged left atrium. We review the use of partial cardiac autotransplantation to reduce left atrial volume in 7 patients with rheumatic mitral valve disease and left atrial and ventricular volume in 2 patients with idiopathic dilated cardiomyopathy. There were 5 males and 4 females aged 25 to 62 years. The patients with rheumatic etiology had atrial fibrillation, while those with dilated cardiomyopathy had sinus rhythm. The mitral valve was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…18,19 Erdogan et al reported similar findings of improvement pre operatively from NYHA functional class III (65%), and 35% were in class II to NYHA class I at six months on follow up. 20 AF usually accompanies MV disease at the time of surgery, especially when the LA is enlarged. This is the main determining factor in the occurrence and maintenance of chronic AF.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Erdogan et al reported similar findings of improvement pre operatively from NYHA functional class III (65%), and 35% were in class II to NYHA class I at six months on follow up. 20 AF usually accompanies MV disease at the time of surgery, especially when the LA is enlarged. This is the main determining factor in the occurrence and maintenance of chronic AF.…”
Section: Discussionmentioning
confidence: 99%
“…My teacher, Arrigo Lessana in Aubervilliers, France, had begun to use partial cardiac autotransplantation in the spring of 1998 [2] for adequate visualization to reduce the size of the left atrium (LA). Later, when I came back to Mexico, I operated on three cases of mitral valve disease and chronic atrial fibrillation (AF) with giant LA from 2000 to 2001 [3]. All three cases had a spectacular outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the left atrium was closed using running 5-0 polypropylene sutures ( Fig. 1) [3]. Finally, through a vertical right atriotomy, a tricuspid annuloplasty was performed with an Edwards MC 3 tricuspid annuloplasty ring (Edwards Lifesciences, Irvine, CA, USA).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac autotransplantation for LA size reduction in patients with AF was designed to obtain significant reduction of LA size, an excellent exposure of the mitral valve, and complete exclusion of AF wavelets around the pulmonic veins. However, due to the aggressiveness and risk of bleeding, reports using this technique are rare …”
mentioning
confidence: 99%